Information about the Zasechnaya Line in the Lower Part of the Volga in the Astrakhan Region (from archival sources and materials of archaeological studies) - Evgeny M. Pigarev (Археология евразийских степей, 2023)
The article considers the Moscow government activities aimed at ensuring the protection of the southern borders of the state, located in the lower part of the Volga River. The given analysis of written sources shows the scale of the works on creation of defensive objects in the XVI – XVIII centuries, included in the state Zasechnaya line, protecting the lands of the Tsardom of Russia from the raids of nomads. A list and a brief description of military fortresses built in the Astrakhan Volga region, such as the Astrakhan Kremlin, the Chetyryohbugorinskoye fortress, Tsaritsyn, Chyorny Yar and Krasny Yar fortresses are given. The author describes the results of studies of the Selitryany town fortress– the only military-industrial facility of the XVIII century, subjected to archaeological study.